Wee sing presents Over in the meadow : a musical story/play - Beall, Pamela Conn.; Nipp, Susan Hagen; Reasoner, Charles; Dana, Katharine Floyd, 1835-1886. (Los Angeles : Price/Stern/Sloan, 1987)
In this musical story based on the traditional song, a young boy visits a meadow with his mother and observes the habits of several animals, from one toad to ten spiders. The story can also be performed as a play.
Song text by Olive A. Wadsworth.
Keywords: Children's songs; Children's plays; Songs; Plays; Animals -- Songs and music; Counting